Predictors and temporal trend of flu vaccination in auto-immune rheumatic diseases in the UK: a nationwide prospective cohort study - Nakafero, Georgina; Grainge, Matthew J.; Myles, Puja R.; Mallen, Christian; Zhang, Weiya; Doherty, Michael; Nguyen-Van-Tam, Jonathan S.; Abhishek, Abhishek (Oxford University Press, 2018)
Objectives: To [1] examine temporal trend in uptake of seasonal influenza vaccine (SIV) in the UK, [2] explore disease and demographic factors associated with vaccination. Methods: 32,751 people with auto-immune rheumatic diseases (AIRDs) prescribed disease modifying anti-rheumatic drugs (DMARDs) between 2006 and 2016 were identified from the Clinical Practice Research Datalink. The proportion vaccinated between 01/September of one year and 31/March of next year was calculated and stratified by age, other indications for vaccination, AIRD type, and number of DMARDs prescribed. Stata and Joinpoint regression programs were used. Results: SIV uptake was high in those aged ≥65 years (82.3% and 80.7% in 2006-07 and 2015-16 respectively). It was significantly lower in other age groups, but improved over time with 51.9% and 61.9% in the 45-64 year age group, and 32.3% and 50.1% in the <45 year age group being vaccinated in 2006-07 and 2015-16 respectively. While 64.9% of the vaccinations in those ≥65 years old occurred by 3rd November, in time to mount a protective immune response before the influenza activity becomes substantial in UK, only 38.9% in the 45-64 year and 26.2% in the <45 year age group without any other reason for vaccination received SIV by this date. Women, those with additional indications for vaccination, on multiple DMARDs and with SLE were more likely to be vaccinated. Conclusion: SIV uptake is low in the under 65s, and the majority of them are not vaccinated in time. Additional effort is required to promote timely uptake of SIV in this population.